Skin metastases in carcinoma of the stomach. Issue 596 (June 1975) - Adam, B. A.; Murugasu, R.
Abstract : A patient who presented with cutaneous nodules had carcinoma of the stomach. The histochemistry of the dermal infiltrate gave a clue to the primary site. Autopsy revealed metastases in all the organs of the chest and abdominal cavity. The invasion of the testis and the gingiva was unusual. Cutaneous metastases from a visceral malignancy probably indicate an early fatal termination. Metastatic lesions to the skin from internal malignancies are rare and the incidence has been reported to vary from one to 2·7% (Gates, 1937; Beerman, 1957). Most reports quote lung and the breast as the primary site of malignancy although other sites including the stomach are not uncommon. The metastases, either single or multiple, may be the initial manifestations of the internal malignancy.